Numerical and Experimental Study on Reasonable Coverage of Shot Peening on ZGMn13 High Manganese Steel - Yuan, Haiyang; You, Zhangping; Zhuo, Yaobin; Ye, Xiaoping; Zhu, Liangliang; Yang, Weibo (Frontiers in Materials, 2022)
In order to improve the ability of mechanical parts to resist fatigue and wear failure, the shot peening technology is usually employed to realize the surface strengthening of target, but the induced residual stress and its distribution with respect to the coverage would affect the performance of the shot peening process. In this study, a comprehensive numerical and experimental study have been conducted to overcome these issues. It has been found from numerical simulation that both the surface and subsurface residual stress increases with the increase of the coverage and then reaches to be stable, and by using the Entropy Method the quantitative analysis indicates that under the shot peening parameters considered in simulation the coverage of 200% is found to be best for the shot peening of ZGMn13 High Manganese Steel. The following experimental study has been found to be agreed with the corresponding numerical data for the residual stresses at varied depth from surface to subsurface with errors of less than 25%. Thus, the related research outcomes can provide the guidance for the shot peening process to obtain the optimized surface strengthening of target.